Efficacy of mifepristone – Prostaglandin analogue combination in medical termination of pregnancy up to and beyond 7 weeks of amenorrhea: The RYMMa study. (November 2020) - Agostini, Aubert; Zinovieva, Elena; Quaranta, Laura Miquel; Herman-Demars, Hélène; Frantz, Sandrine; Sicot, Marie; ,
Abstract: Objective: To assess, in real-life conditions, the success rate of the protocol mifepristone 600 mg / prostaglandin analogue (PG) in women requesting medical termination of pregnancy (MToP) either up to or beyond 7 weeks of amenorrhea (WA). Study design: The study was performed between 2015 and 2016. This was a non-interventional prospective, multicentre, longitudinal study conducted in France, among a sample of public and/or private centres dealing with MToP. Characteristics of women, term of Mtop, modality of PG used were reported. The primary outcome was success of MToP, defined as complete abortion without surgical procedure. Results: A total of 893 pregnant women with less than the legal term of 14 WA were included in this study: 490 (54.9 %) ≤7 WA and 403 (45.1 %) >7 WA comprising 29 > 9 WA. The mean age of women was 28.1 ± 6.8 years and the one of pregnancy was 7.0 WA ± 1.3 WA. The most frequently used PG combined to mifepristone 600 mg was misoprostol 400 μg (57.0 % ≤7 WA and 35.1 % >7 WA) or 800 μg per os (oral or oral transmucosal) (27.5 % ≤7 WA and 40.1 % >7 WA). Vaginal misoprostol (6.4 %, N = 48) and gemeprost (5.2 %, N = 39) were less used. In women ≤7 WA (N = 422) and women >7 WA (N = 354) for whom result of the MToP was collected, success rates were 94.5 % (95 %CI 91.9 %–96.5 %) and 92.4 % (95 %CI 89.1 %–94.9 %), respectively (p = 0.219). In multivariate regression analysis, three factors were significantly associated with a higher risk of MToP failure: increased number of previous pregnancies (OR = 1.233; 95 %CI 1.086–1.401 for one pregnancy), increased number of previous surgical ToPs (OR = 1.563; 95 %CI 1.036–2.359 for one ToP) and increased interval between mifepristone and PG intake (OR = 1.061; 95 %CI 1.012–1.112 for one hour). Term of pregnancy (OR = 1.497; 95 %CI 0.833–2.690 for ≤7 WA vs >7WA), administration route (OR = 1.553; 95 %CI 0.488–4.936 for oral vs oral transmucosal; and OR = 1.216; 95 %CI 0.625–2.366 for vaginal vs oral transmucosal), and dose of misoprostol (OR = 1.000; 95 %CI 0.999–1.001), were not associated with the risk of failure. Overall, tolerance was good. Conclusion: This study showed, in real-life settings, a high rate of success for MToP using mifepristone 600 mg, independent of the pregnancy term and the therapeutic protocol used. MToP was safe and well tolerated however only a small number of women beyond 9 WA have been included.